Equilíbrio corporal de indivíduos com doença de Parkinson - Flores, Franciele da Trindade (2009)
Body balance is the ability people have to keep themselves erect or to perform acceleration movements and rotation without oscillation or fall. Balance alterations can happen due to a problem in one or more of the systems and then the person complain of imbalance. Parkinson s disease (PD) can be included among the multiple causes that lead to changes in body balance, considering that this disease is defined as a progressive neurological disorder, essentially with motor symptoms. The alterations in body balance cause resting tremor, rigidity, akinesia, failure of postural reflexes and walking and balance instability, among others. Thus, because of the close relationship between Parkinson's disease and vestibular and body balance changes, this study aims at evaluating body balance in Parkinson s patients. The study group contained twelve participants with Parkinson s disease, from the neurology sector at the University Hospital in Santa Maria. They were assessed based on anamnesis, static and dynamic balance tests, coordination, dynamic posturography and vestibular test. In order to compare the results from the dynamic posturography, there was a paired control group. Results: The main vestibular problems by Parkinson s patients were: balance problems (100,00%), dizziness (75,00%), imbalance while walking (75,00%), gait deviation (50,00%), tendency to fall (41,66%), vertigo (25,00%) and instability (25,00%); besides this, tremor (100,00%), rigidity and difficulty with movements (83,33%), problems to begin movements and problems with the gait(100,00%). Significant changes were found in Romberg-Barré, Untemberg and Walking tests, and there were 6 cases with normal vestibular examination, 4 with central vestibular syndrome and 2 cases of peripheral vestibular syndrome. In the dynamic posturography, it was verified balance instability if compared to the control group in terms of the Sensory Organization Test (SOT), in the average and the use of the vestibular system. Conclusion: The main vestibular complaints from Parkinson s patients are problems with balance, dizziness, imbalance while walking, gait deviation, tendency to fall, vertigo and instability. The dynamic posturography was more accurate to detect alterations in body balance than the vectoelectronistagmography.